Zurechnungsfragen des Betrugstatbestands - Rennicke, Jan (Schriften zum Strafrecht, 2021)
»Questions of Imputation in the offense of Fraud«: The thesis examines classic and modern problems of the offense of fraud under the lense of methods of imputation provided by the General Part of the Criminal Code. Among other topics, it deals with the imputation of knowledge within organizations (e.g. corporations) and the question of accountability in complex constellations with three or more parties involved in a fraudulent action.